2016
DOI: 10.1007/s00170-016-8583-7
|View full text |Cite
|
Sign up to set email alerts
|

Research on surface topography in ultra-precision flycutting based on the dynamic performance of machine tool spindle

Abstract: The dynamic performance of ultra-precision cutting machine tools is an important factor for its machining accuracy. To improve the precision of the machine tool, a surface topography model is built in this paper and the tool path during the cutting process is achieved by dynamic finite element analysis (DFEA) of the air spindle in ANSYS, surface topography is obtained using MATLAB simulation by combing the model with the tool path, and an experiment is carried out for validation. Results show the simulation su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…In the authors' related studies, [17][18][19] it has been confirmed that the most typical medium-frequency waviness along the cutting direction is produced by the vibration of the spindle. The mechanism of the vibration has been defined as well.…”
Section: Introductionmentioning
confidence: 87%
“…In the authors' related studies, [17][18][19] it has been confirmed that the most typical medium-frequency waviness along the cutting direction is produced by the vibration of the spindle. The mechanism of the vibration has been defined as well.…”
Section: Introductionmentioning
confidence: 87%
“…Surface profiling shows that on a microscopic scale, as magnification increases, a surface profile does not tend to be a straight line but instead maintains an approximately similar shape. The state where a part of an object is similar to the whole in a certain way is called fractal, and the fractal geometry has self-similarity and scale invariance [17]. The fundamental principle of the fractal method is as follows,…”
Section: Fundamental Theory Of the Fractal Methodsmentioning
confidence: 99%
“…1,2 In particular, the dynamic performance of the ultra-precision flycutting machine tool has a significant impact on the surface quality due to its special processing way. 3 Large diameter optical components processed by the ultra-precision flycutting machine tool can achieve high accuracy, which surface accuracy is less than 1 mm, and the roughness is less than 3 nm. Chen et al 4,5 presented a two-round method to design a flycutting machine tool, and further studied the multi-mode vibration of the machine tool and its influence on surface generation.…”
Section: Introductionmentioning
confidence: 99%